2018
DOI: 10.1007/s00429-018-1737-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and glucocorticoid-dependent regulation of the stress-inducible protein DRR1 in the mouse adult brain

Abstract: Identifying molecular targets that are able to buffer the consequences of stress and therefore restore brain homeostasis is essential to develop treatments for stress-related disorders. Down-regulated in renal cell carcinoma 1 (DRR1) is a unique stress-induced protein in the brain and has been recently proposed to modulate stress resilience. Interestingly, DRR1 shows a prominent expression in the limbic system of the adult mouse. Here, we analyzed the neuroanatomical and cellular expression patterns of DRR1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The images of Figure 3 display nuclear localization of Actin, consistent with other reports [53]; DRR1 also has been reported to be both in the nuclear and cytosolic compartment [25,47,54]. We performed biochemical fractionation of HEK-293 cells ectopically expressing wt or mutant DRR1 to analyze the nuclear and cytosolic fraction by Western blotting (Figure A2).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The images of Figure 3 display nuclear localization of Actin, consistent with other reports [53]; DRR1 also has been reported to be both in the nuclear and cytosolic compartment [25,47,54]. We performed biochemical fractionation of HEK-293 cells ectopically expressing wt or mutant DRR1 to analyze the nuclear and cytosolic fraction by Western blotting (Figure A2).…”
Section: Resultssupporting
confidence: 85%
“…Other studies reported changes of actin regulatory proteins by antidepressants and mood stabilizers [85,86] mutations in genes of the regulatory network of the actin cytoskeleton appear to be enriched in treatment-resistant major depression [87]. Pathway-based methods to genetic data have been suggested to blend biological information with the power of –omics approaches [83]; we propose that the stress- and glucocorticoid-regulated DRR1 [22,23,47,88] should be included when analyzing the role of the actin cytoskeleton in physiology and pathology, particularly in stress-related processes. Furthermore, since actin regulatory factors work in concert, future biochemical investigation of DRR1 should include the combination with additional actin binding proteins, as this study now firmly established DRR1 as an actin-regulatory protein.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is well established to mimic stress situations in rodents via subcutaneous (s.c.) injections. In vivo DEX injections elevated DRR1 mRNA throughout the whole murine brain 8 h post-injection (Masana et al, 2018). Significant elevations were especially found in brain areas with high basal DRR1 expression such as the hippocampal CA3-region (Masana et al, 2018).…”
Section: Stressed Hippocampal Neuron Cultures and Drr1mentioning
confidence: 96%
“…For that, we applied DEX onto primary hippocampal cultures after 12-13 DIV for either 24 h or 48 h. Subsequently, cells were lysed at DIV 14 and Western Blot analysis were performed to evaluate DRR1 and GluR2 protein amounts. Previous in vivo experiments utilized a concentration of 10 mg/kg body weight (Masana et al, 2018). Literature reveals an apoptotic effect after DEX-treatment on chondrocytes starting at 25 µM concentrations after 48 h of application (Chrysis et al, 2005).…”
Section: Stress Induced By Dex Leads To Increased Drr1 and Glur2 Prot...mentioning
confidence: 99%